Efek Mutagenik Ekstrak Etanol Daun Kembang Sungsang (Gloriosa superba L.) - Sundari, Dian; Pudjiastuti, Pudjiastuti (Jurnal Kefarmasian Indonesia, 2009)
Eﬂicacy of a plant can be caused by chemical compounds contain, on the other hand can cause toxic eﬂects. Toxic ejfects of chemicals can be deﬁned as the potential of chemicals to poison the bodies of people who are exposed kembang sungsang (Gloriosa superba Linn.) including Colchicaceae families. Plants used empirically for treatment of Gout, diuretic, rheumatism, etc. Mutagenicity is a test to determine the possibility of compounds are mutagens. To see if these plants have the effect of mutagens, mutagenicity tests performed 70% ethanol extract of the leaves Kembang sungsang. Mutagenicity studies conducted by the Ames method using ﬁve test bacterial strains that have been transferred are.‘ Salmonella typhimurium TA 98, TA 100, TA 1535, TA 1537 and Escherichia colt WP2uvrA with and without metabolic activator S-9. The dose tested was 125, Z50, 500, 1000, and 2000 ul /plate. As a negative control was DMSO solution of 100 ul /plate. The results showed that the mutagenic test 70% ethanol extract of leaves Kembang sztngsang. with the addition aktivator without the addition of S-9 did not have the eﬂect of mutagens.